OPTIMASI PERFORMA LASER CUTTING ENGRAVING DENGAN DAYA LASER 6.5 WATT PADA MATERIAL AKRILIK MENGGUNAKAN METODE TAGUCHI - Bagas Jaya Buwono (2020)
In this time laser cutting machining processes are often utilized in large industries as well as individual and student scientific projects. Acrylic is one of the materials whose processing involves a lot of laser cutting, but today many laser cutting, especially low-power ones are not optimally optimized. In this study, the author wants to optimize the laser cutting with 6.5 Watt power using the Taguchi optimization method on solid black acrylic material with a thickness of 3mm, with reference to the surface roughness value of the workpiece after being subjected to the laser cutting process using the Ra unit. The control factors included are laser distance, laser power, cutting speed and cooling time. The experimental process was carried out 27 times with replication measurements 2 times. The best results from experiments with a roughness measurement value of 0.782 µm while the average roughness value was 2.271 µm. After conducting experiments it is known that the best results are obtained with a laser distance factor of 20.6mm, a cutting speed of 70mm / min, a laser power of 6.5 watts and a cooling time of 10s. while the influence of factors on the results of surface roughness is a laser distance of 27%, cutting speed of 40.9%, laser power of 18.9% and cooling time of 7.05%. after caliberation on laser cutting the accuracy of cutting increases from ± 1mm to ± 0.4mm or increases by 60%, with an average final dimension measurement of 24.87mm.